A STUDY ON SPOKEN LANGUAGE ELEMENTS IN THE WRITTEN EXPRESSIONS OF SECONDARY SCHOOL STUDENTS - Özgür İLANBEY; Remzi CAN (Zeitschrift für die Welt der Türken, 2016)
In this study, the spoken language elements used by the second stage primary education students in their written expressions were determined and classified in accordance with the spoken language elements stated in the related literature. The use of written language in a clear, understandable way and away from arbitrariness, which will not cause any communication problems, contributes to the improvement of the written skills. It is believed that the determination of the spoken language elements in the students’ written expressions and the elimination of the problems will be effective in the improvement of the written expression skills. The sample of the study comprises 201 students of the 5th and 8th grades from the secondary schools, two of which are located in the center of Kırşehir and three in the villages of the other provincial districts. The study reflects a descriptive situation analysis. Document review technique was used in the determination and analysis of the data. The data was evaluated separately as the 5th and 8th grades in accordance with classroom levels and as the city and village in accordance with the residential area. As a result of the study, it was seen that the elements of the spoken language were frequently used by the students in their written expressions and that these usages showed variety.